Hasimoto Maps for Nonlinear Schrodinger Equations in Minkowski Space - Gurbuz, Nevin Ertug; Yuzbasi, Zuhal Kucukarslan; Yoon, Dae Won (Springernature, 2022)
In this paper, we study the vortex filament flow for timelike and spacelike curves in Minkowski 3-space. The vortex filament flow equations of the timelike and the spacelike curves are equivalent to the nonlinear Schrodinger equation and the heat equation, respectively. As a consequentce, we prove that a soliton of the nonlinear Schrodinger equations of the timelike curve gives a solution of a traveling wave on a line at infinity. Also, we study a solution of a traveling wave of the nonlinear Schrodinger equations of the spacelike curve in terms of a new complex frame. Finally, we discuss the method to find the exact shape of the timelike and the spacelike curves from the vortex filament by solving the Frenet vectors of these curves and provide applications to illustrate the method.
Keywords: Hasimoto map; Nonlinear Schrodinger equation; Travelling wave; Binormal flow; Evolution equation